Crime Impact Model of Narcotic Drug Abuse in Nigeria - Akpienbi, Isaac Oritsejubemi; Jude, Iroka (Darul Yasin Al Sys, 2024)
This study developed a 6-dimensional nonlinear ordinary differential equation model to investigate the criminal activity associated with narcotic drug abuse in Nigeria. The model was structured around the dynamics of disease transmission, with the goal of limiting and potentially eliminating the threat posed by drug abuse crimes. The analysis of the basic reproduction number, R0, revealed that narcotic drug abuse will die out when R0<1, and become endemic when R0>1. The model’s stability analysis showed that the narcotic drug abuse-free equilibrium is asymptotically stable when the Routh-Hurwitz criteria are satisfied. The study emphasizes the importance of consistent law enforcement, effective rehabilitation programs, and a coordinated, multi-sectoral approach to addressing the escalating narcotic drug abuse crisis in Nigeria. The findings of this research are recommended for consideration by policymakers, public health professionals, and community stakeholders to mitigate the far-reaching consequences of this pressing issue. The use and trafficking of narcotic drugs have emerged as a growing public health and social concern in Nigeria in recent years. The misuse of narcotics, including substances such as opioids, cannabis, and cocaine which is alarming in the preval_ence of narcotic drug abuse across the country, with profound implications for individual well-being, public safety, and socioeconomic development.